Long-term marine resource use in Hokkaido, Northern Japan: new insights into sea mammal hunting and fishing. Issue 3 (27th May 2019) - Takase, Katsunori
ABSTRACT: Based on examinations of archaeofaunal remains from 153 components from 122 sites in Hokkaido, Northern Japan, this study highlights that northern fur seals were the most important game for sea mammal hunting from the early Early Jomon (7000 calBP) and proposes a hypothesis that offshore hunting technology for hunting adult fur seals was established prior to the late Early Jomon (5800 calBP). This study also reveals that the importance of fishing for subsistence rapidly increased during the very end of the Final Jomon (2600 calBP) and the Early Epi-Jomon (2400 calBP–1800 calBP). Fishing focusing on bastard halibut and swordfish was actively conducted for status-building by Early Epi-Jomon fishers in some areas. Mortuary analyses indicate that ritual leaders were not necessarily capable fishers and/or hunters in the Jomon communities. However, during the Early Epi-Jomon, only successful fishers and/or hunters had the power to control rituals and the long-distance trade.